2010
DOI: 10.1899/09-097.1
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of a translocation between two divergent lineages of theParatya australiensis(Decapoda:Atyidae) complex: reproductive success and relative fitness

Abstract: When 2 populations are mixed for whatever reason, the outcome can be difficult to predict. In 1993, 2 populations of an atyid shrimp (Paratya australiensis:Atyidae) from different subcatchments of the Brisbane River, Queensland, Australia, were mixed as a result of a translocation. At the time, they were thought to represent slightly divergent populations of a single species. However, subsequent molecular analysis showed that they were significantly divergent. An analysis of patterns at one of the sites in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…Indeed, this has been suggested as important in the distribution of atyid shrimps by previous authors based on laboratory experiments on the two lineages (Fawcett et al. ).…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, this has been suggested as important in the distribution of atyid shrimps by previous authors based on laboratory experiments on the two lineages (Fawcett et al. ).…”
Section: Discussionmentioning
confidence: 79%
“…An early study showed that some hybridization between the lineages had occurred but that lineage 4 had dispersed more than 1.5 km upstream of the translocation site and had sent lineage 6 almost extinct in all sites higher and 2 sites lower of than the original translocation site (Hughes et al, 2003). Two years later, lineage 4 sill dominated high elevation sites (In the Branch Creek-translocated stream) but had not moved further to low elevation sites (Fawcett, Hurwood & Hughes, 2010). It was hypothesized that lineage 4 is adapted to higher elevations, as they quickly colonized the upper reaches of the stream which is approx.…”
Section: Introductionmentioning
confidence: 99%
“…This was supported by a small laboratory experiment in which individuals of the 2 lineages were incubated in separate tanks and water temperature was increased by 1 • C every 3 days. Lineage 4 was less tolerant to increasing temperature than lineage 6, dying at a lower temperature (Fawcett, Hurwood & Hughes, 2010). Ten years later, in Branch Creek following very heavy rainfall over 2 summers, lineage 4 had shifted further to downstream, which was suspected to be due to lower temperatures caused by heavy rainfall (Wilson, Schmidt & Hughes, 2016), favoring lineage 4 over lineage 6.…”
Section: Introductionmentioning
confidence: 99%
“…Paratya australiensis (Decapoda: Atyidae) is a small freshwater shrimp which is widespread in eastern Australia (Williams andAltmann 1980, Choy andHorwitz 1995) and is one of the most conspicuous and abundant macroinvertebrates in small headwater streams in southeastern Queensland (Hancock and Bunn 1997). The species has been extensively studied in terms of genetics, dispersal, behaviour and systematics (Hughes et al 1995, Baker et al 2004, Fawcett et al 2010, Bool et al 2011), but its role in transforming periphyton and sediments has not been studied experimentally.…”
Section: Introductionmentioning
confidence: 99%